A second locality for the Namib darkling beetle Onymacris brainei (Tenebrionidae, Coleoptera) and first report on its molecular phylogenetic placement - Lamb, Trip; Marais, Eugene; Bond, Jason E. (My University, 2017)
Onymacris brainei Penrith, 1984 – the most recent species of Onymacris to be described – is known only from its type locality in the Namib Desert, adjacent to the Cunene River in northern Namibia. No additional specimens are known to have been collected beyond the type series. Herein, we report on eight specimens discovered at a second site near the original locality. DNA from four beetles was used to determine the phylogenetic placement of O. brainei among congeners, based on sequence data from one nuclear (histone III) and two mitochondrial (cox1, cox2) genes. Maximum likelihood analysis identifies O. brainei as a member of the ‘white’ Onymacris clade, in which it forms a strongly supported subclade with O. bicolor and O. marginipennis. More broadly, its phylogenetic placement augments previous molecular results that revealed a sister taxon relationship between the ‘white’ Onymacris and a second genus, Physadesmia. The paraphyly of Onymacris with respect to Physadesmia highlights a need for nomenclatural change, but revision should await acquisition of genetic data for the few species outstanding in both genera.
Supported by the ECU's Open Access Fund
Keywords: Adesmiini; Namib Desert; Tenebrionidae